Male courtship rate plasticity in the butterfly Bicyclus anynana is controlled by temperature experienced during the pupal and adult stages. - Ashley Bear (Public Library of Science (PLoS), 2013)
Environmental cues can act to initiate alternative developmental trajectories that result in different adult phenotypes, including behavioral phenotypes. The developmental period when an organism is sensitive to the cue is often described as a critical period. Here we investigated the critical period for temperature-sensitive courtship rate plasticity in the butterfly Bicyclus anynana. We performed a series of temperature-shift experiments in which larvae, pupae, or adults were shifted for blocks of time from one temperature to an alternative temperature, and then we quantified the courtship rate exhibited by adult males. We discovered that the critical period begins during pupal development and extends into adulthood, but temperature experienced during larval development does not affect male courtship rate. This finding allows us to develop hypotheses that address how developmental and physiological factors may have influenced the evolution of behavioral plasticity in this species.